Biocatalytic preparation of a key intermediate of antifungal drugs using an alcohol dehydrogenase with high organic tolerance. (9th November 2021) - Yan, Jinrong; Wang, Xiaojing; Li, Fangling; Yang, Lei; Shi, Guixiang; Sun, Weihang; Shao, Lei; Huang, Junhai; Wu, Kai
Graphical abstract: Abstract: In this study, an alcohol dehydrogenase derived from Lactobacillus kefir (LkADH) was engineered and a simple and practical bioreduction system was developed for the preparation of ( R )-2-chloro-1-(2, 4-dichlorophenyl) ethanol (( R )-CDPO), a key intermediate for the synthesis of antifungal drugs. Through active pocket iterative saturation mutagenesis, mutant LkADH-D18 (Y190C/V196L/M206H/D150H) was obtained with high stereoselectivity (99% ee, R vs 87% ee, S ) and increased activity (0.44 µmol·min −1 ·mg −1 ). LkADH-D18 demonstrated NAD(P)H regeneration capability using a high concentration of isopropanol (IPA) as a co-substrate. Using 40% IPA (v/v), 400 mM of ( R )-CDPO (90.1 g·L -1 ) was obtained via complete substrate conversion using 40 mg·mL −1 LkADH-D18 wet cells. The biocatalytic process catalyzed at constant pH with the cheap co-solvent IPA contributed to improved isolated yield of ( R )-CDPO (97%), lower reaction cost, and simpler downstream purification, indicating the potential utility of LkADH-D18 in future industrial applications.